2018
DOI: 10.3892/ijmm.2018.3658
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑381/Hes1 is a potential therapeutic target for spinal cord injury

Abstract: The aim of the present study was to investigate whether microRNA‑381 is a potential therapeutic target for spinal cord injury (SCI) and its possible mechanism. Reverse transcription quantitative polymerase chain reaction (qPCR) for mRNA expression was used to analyze the changes of microRNA-381 expression. Cell viability and cell apoptosis were measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and flow cytometry. Caspase‑3 activity was measured using caspase‑3 activity kit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Besides, the HES1 upregulation has been detected in mice with TB1 by the research of Wang et al [ 33 ]. Consistently, a prior research suggested that HES1 overexpression was involved in promotion of neuronal apoptosis in rats with spinal cord injury [ 34 ].…”
Section: Discussionsupporting
confidence: 76%
“…Besides, the HES1 upregulation has been detected in mice with TB1 by the research of Wang et al [ 33 ]. Consistently, a prior research suggested that HES1 overexpression was involved in promotion of neuronal apoptosis in rats with spinal cord injury [ 34 ].…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, a high-throughput screening study was able to identify the expression pattern of additional hypothalamic sets of miRNAs, including let-7a, miR-9, miR-30e, miR-132, miR-145, miR-200a, and miR-218, which were altered by caloric restriction and/or a high-fat diet [ 39 , 40 ]. Moreover, association of miR-96/182/183 cluster, miR-141/200c cluster, miR-200a/200b/429 cluster [ 41 ], miR-142 and miR-376c [ 42 ], microRNA 381/Hes1 [ 43 ], miR-361-3p [ 44 ], and miR-219 [ 45 ] was linked with the development of hypothalamic abnormalities in various studies. Furthermore, recent studies found that hypothalamic miR-141 [ 46 ], miR-326 [ 47 ], miR-34b, miR-326, miR-432, miR-548c-3p, miR-570, miR-603 [ 48 ], miR-488, miR-144, miR-542-5p, miR-421, miR-376b-5p [ 49 ], miR-543-5p [ 50 ] [ 51 ], and miR-363-3p [ 52 ] are potential contributors in different neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Though still in animal experiment stage, an increasing number of studies have confirmed this hypothesis. 3440 In this study, the transferred M2 cells could promote ncRNA metabolic process and ncRNA processing. This may be a reasonable explanation for the adoptive immunization of M2 cells to promote SCI repair.…”
Section: Discussionmentioning
confidence: 82%